Community Religious Behavior Towards Offersings In Marriage - Khoiriyah, Laili; Pramesti Cahyani, Regita; Tharafa Danna, Yamna (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Theoretically, most village people still maintain traditions from their ancestors. As happened in the people of Kedungwaru Kidul who have various views regarding offerings with the aim of maintaining the tradition of offerings. Offerings at a wedding in Kedungwaru Kidul Village, Karanganyar District, Demak Regency. The problem studied in this research is to know the behavior of the Kedungwaru Kidul community and the religious practices of the community towards wedding offerings. In the formulation of the problem there is a sub-discussion in it which contains people's opinions regarding offerings in marriage. In this study using qualitative methods by collecting some observational data and interviews, in compiling this data is done in the field with the aim to provide answers to existing questions. From the results of this study, it is explained that offerings are a culture of the ancestors passed down from one generation to the next. Offerings can be interpreted as an expression of gratitude to God, and given smoothness in the wedding ceremony that will be held. In addition, these offerings are commemorated as a sense of respect for the ancestors.